Hubungan Asupan Makanan Cepat Saji (Fast Food) dengan Status Gizi Mahasiswa Fakultas Kedokteran - Ertati Suarni; Risdiansyah Risdiansyah; Elvina Monica (Lontara Journal of Health Science and Technology, 2026)
Fast food is a practical type of food that is increasingly consumed by university students, including medical students who have dense academic activities. Excessive fast food consumption may affect nutritional status. This study aimed to determine the relationship between fast food consumption and nutritional status among students of the Faculty of Medicine, Universitas Muhammadiyah Palembang. This was an observational analytic study with a cross-sectional design. The subjects were students who met the inclusion and exclusion criteria. Data on fast food consumption were collected using a Food Frequency Questionnaire (FFQ), while nutritional status was determined based on Body Mass Index (BMI). Data were analyzed using univariate and bivariate analysis with the Chi-Square test. The results showed a significant relationship between fast food consumption and nutritional status among students of the Faculty of Medicine, Universitas Muhammadiyah Palembang (p < 0.05).